SUBSYSTEM OF SUPPORT OF DECISION-MAKING IN ORGANIZATION OF MILITARY SUPPORT OF SOLDIERS (DEPARTMENTS) OF AIR COMMANDING IN AIR TRAFFIC - Drobakha, G. А.; Gurin, О. М. (Honor and Law, 2019)
In the article, based on the studies conducted to build a rational structure of the material support system for military units (divisions) of the air command in an air operation, the questions of building a subsystem of decision support for its organization will be revealed. A set of tasks for this subsystem is developed. The possibility of algorithmic realization and further use in the decision support system of the commander of the air command in the perspective automated control system of aviation and air defense is substantiated.